2020
DOI: 10.1532/hsf.3109
|View full text |Cite
|
Sign up to set email alerts
|

Sternum Dehiscence: A Preventable Complication of Median Sternotomy

Abstract: Background: The incidence of sternal dehiscence following cardiothoracic surgery via sternotomy is rare. It causes serious patient dissatisfaction and leads to higher hospital costs. For years, each clinic has made efforts to reduce this complication. Here, we aimed to summarize our techniques to prevent dehiscence. Material: This retrospective study included two groups operated via median sternotomy from March 2009 to May 2019. The first group included 1,105 consecutive patients who only received sternum wire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Previously identified risk factors for dehiscence include chronic obstructive pulmonary disease, pneumonia, and prolonged mechanical ventilation. [2][3][4]8,10,12,[18][19][20] Our study found that the number of ventilator days was significantly greater in those with sternal aseptic osseous dehiscence than all other complication types and the matched comparator group, which affirms previous research that prolonged ventilation is a risk factor for dehiscence. Additionally, coughing has been shown to result in sternal forces substantially greater than upper extremity movements.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previously identified risk factors for dehiscence include chronic obstructive pulmonary disease, pneumonia, and prolonged mechanical ventilation. [2][3][4]8,10,12,[18][19][20] Our study found that the number of ventilator days was significantly greater in those with sternal aseptic osseous dehiscence than all other complication types and the matched comparator group, which affirms previous research that prolonged ventilation is a risk factor for dehiscence. Additionally, coughing has been shown to result in sternal forces substantially greater than upper extremity movements.…”
Section: Discussionsupporting
confidence: 89%
“…Given that there were no instances of documented noncompliance (ie, increased number of cues or other documented comments/concerns) in those with aseptic osseous dehiscence and no clear differences in functional status in patients with other complication types, other clinical characteristics not fully accounted for in this study may have contributed to the aseptic sternal osseous dehiscence. Previously identified risk factors for dehiscence include chronic obstructive pulmonary disease, pneumonia, and prolonged mechanical ventilation 2-4,8,10,12,18-20. Our study found that the number of ventilator days was significantly greater in those with sternal aseptic osseous dehiscence than all other complication types and the matched comparator group, which affirms previous research that prolonged ventilation is a risk factor for dehiscence.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…17 With the high burden of SSIs, attention to patient perioperative risk and the use of enhanced preventive techniques can assist in preempting the incidence of sternal instability and dehiscence. 18 In this pilot study, 16 consecutive patients with SSCs following intracardiac surgery underwent chest wall reconstruction using muscle advancement flaps followed by surgical incision management using a ciNPT specialty dressing with ciNPT over a revised median sternotomy incision. The use of ciNPT with the specialty dressing was associated with a 93.8% intact incision rate at the initial dressing change (POD 7) and at the 30-day follow-up appointment.…”
Section: Discussionmentioning
confidence: 99%
“…Age is one of the known factors associated with inadequate early healing, according to the literature(17)(18). In comparison to the Steel Wire group of the UHMWPE Cerclage Sternal Band product, the statistically significant data indicated above is determined to be successful.Obese patients had a higher risk of wound infection and sternal separation following heart surgery(19,20). Compared to the patients in the Steel Wire group, the UHMWPE Cerclage Band group's obesity levels were statistically higher.…”
mentioning
confidence: 94%